ANALISIS EFEKTIVITAS PEMANFAATAN TEKNOLOGI DIGITAL DALAM PROSES PEMBELAJARAN MATEMATIKA DI TINGKAT SEKOLAH DASAR - Rafika Dian Rahmawati; Markhamah; Ahmad Fathoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Exploring the use of digital technology in mathematics learning in primary schools has attracted the interest of practitioners and education policy makers. This study aims to assess how effective the use of digital technology is in the learning process of mathematics at the primary school level, as well as identify supporting factors that can strengthen the integration of digital technology in learning. The research method applied is a systematic literature review (SLR). Through SLR, researchers collected and evaluated various studies relevant to this particular topic. By using digital technology in mathematics learning, students can be more interested and actively involved in the learning process. The results of this study show that utilizing digital resources can improve students' ability to think critically when dealing with mathematical materials. The findings are expected to provide inspiration for educators in developing more effective learning innovations.